Synbiotic, probiotic and neem leaf as alternatives to antibiotic growth promoter in broiler diet - Ahammed, M; Rahman, MN (Bangladesh Journal of Animal Science, 2022)
The feeding trial was carried out to compare the effect of probiotic, synbiotic and neem (Azadirachta indica) leaf as alternatives to antibiotic in broiler chicken diets. The experiment was performed for a period of 28 days with a number of 500 day-old straight run broiler chicks. Birds were divided into five dietary treatment groups with 4 replications having 25 birds in each. The dietary groups were; control (Basal diet), synbiotic, probiotic, neem leaf powder (NLP) and antibiotic group. The experimental diets were consisted as broiler starter (day-old to 14 days) and broiler grower (15 to 28 days). The supplementation of synbiotic, probiotic, NLP and antibiotic in the broiler diets had significant effect on growth performance. Diets supplemented with synbiotic showed significantly (p<0.05) higher live weight and weight gain at the end of the experiment compare to the control and antibiotic group. NLP and probiotic supplemented groups also showed significantly higher (p<0.05) body weight and body weight gain compared to control and showed almost similar performance compared to antibiotic group. Better FCR (p<0.05) was also noticed in synbiotic group (1.60) compare to the control (1.79), antibiotic group (1.65), NLP group (1.69) and probiotic group (1.70). There were no significant differences in meat quality characteristics among the dietary groups. The cost of production per kg of live broiler was slightly lower in synbiotic group compared to control and antibiotic groups. With regards to profit, synbiotic groups showed higher profitability than other groups. The result indicated that supplementation of synbiotic, probiotic and NLP in broiler diet had a positive effect on growth performance and profitability. It is therefore suggest that the synbiotic, probiotic and NLP could be potential feed additives in broiler diet and synbiotic could be considered as a better antibiotic alternative for broiler production. Bangladesh Journal of Animal Science 51 (3): 122-132, 2022